INTERNATIONAL FINANCIAL REPORTING STANDARDS IN THE SYSTEM OF ACCOUNTING AND CONTROL OF BANK LENDING TO THE AGRICULTURAL SECTOR - HAVRYLENKO, Valentina; CHIZH, Vera; TKACHENKO, Alla; HORBENKO, Marharyta (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the theoretical and applied aspects of accounting and control of banking operations related to the financing of Ukraine’s agricultural sector. It establishes the importance of bank lending in supporting the activities of agricultural enterprises, particularly under conditions of wartime risks and post-war economic recovery. The study analyzes regulatory requirements and accounting standards for bank loans, highlighting the specifics of loan recognition in the accounting systems of agricultural enterprises in accordance with national accounting standards and International Financial Reporting Standards (IFRS). Mechanisms for credit operations control are examined—both from the side of banks (monitoring the targeted use of loans, assessing borrowers’ creditworthiness, managing credit risk) and borrowers (internal financial control, debt servicing planning, and timely repayment). The main challenges in credit support for the agricultural business are outlined: high cost of credit, insufficient collateral, elevated default risks, and limited access to banking finance for small and medium-sized enterprises. Particular attention is paid to analyzing public policy in the sphere of financial and credit support of agribusinesses, especially the role of state programs, guarantee mechanisms, and agricultural insurance. Based on a synthesis of scholarly publications and statistical data, the article provides recommendations for improving accounting and control of banking operations related to agrarian credit. These include implementing international standards, increasing financial reporting transparency, strengthening internal financial control, developing risk management tools, and enhancing coordination between banks, agricultural enterprises, and the state. These measures will contribute to reducing risks, improving access to finance for agribusinesses, and strengthening the financial resilience of the agricultural sector amid wartime challenges and economic instability.